(untitled) (Journal of Imam Al-Kadhim College, 2024)
Thes research talking about the topic of interpretation of epidemics especially the plague, according to Muslim historians. this topic that historians have many written about until they provided many details about its spread and the reasons for its acquisition. They were forced to attribute the cause of this epidemic to an unseen reason, as it was transgressed by one of God’s soldiers who takes revenge on those. Those who ruled against immoral acts, were addicted to sins, and openly committed them, driven by their religious and mental culture. idiologies that characterize them and stemming from their faith, being the natural and inherited epidemics that strike people throughout the era of the Islamic State and its long life, are only an punishments for sinners and alert the unwary, without confirming its causes wether its natural,as it was affected by disasters and epidemics Even though we believe that everything is in the hands of God and He is the owner of everything in the universe and directs it according to His will, here we are looking through this study to show that these metaphysical explanations do not contradict the saying that everything that occurs in the universe has natural causes for its formation, far from Non-material - metaphysical - reasons, and the study attempts to explain those reasons